Effects of Erythropoietin on Frataxin Levels and Mitochondrial Function in Friedreich Ataxia – a Dose–Response Trial - Nachbauer, Wolfgang; Hering, Sascha; Seifert, Markus; Steinkellner, Hannes; Sturm, Brigitte; Scheiber-Mojdehkar, Barbara; Reindl, Markus; Strasak, Alexander; Poewe, Werner; Weiss, Guenter; Boesch, Sylvia (Cerebellum (London, England), 2011)
Friedreich ataxia (FRDA) is an autosomal recessive inherited neurodegenerative disorder leading to reduced expression of the mitochondrial protein frataxin. Previous studies showed frataxin upregulation in FRDA following treatment with recombinant human erythropoietin (rhuEPO). Dose–response interactions between frataxin and rhuEPO have not been studied until to date. We administered escalating rhuEPO single doses (5,000, 10,000 and 30,000 IU) in monthly intervals to five adult FRDA patients. Measurements of frataxin, serum erythropoietin levels, iron metabolism and mitochondrial function were carried out. Clinical outcome was assessed using the “Scale for the assessment and rating of ataxia”. We found maximal erythropoietin serum concentrations 24 h after rhuEPO application which is comparable to healthy subjects. Frataxin levels increased significantly over 3 months, while ataxia rating did not reveal clinical improvement. All FRDA patients had considerable ferritin decrease. NADH/NAD ratio, an indicator of mitochondrial function, increased following rhuEPO treatment. In addition to frataxin upregulation in response to continuous low-dose rhuEPO application shown in previous studies, our results indicate for a long-lasting frataxin increase after single high-dose rhuEPO administration. To detect frataxin-derived neuroprotective effects resulting in clinically relevant improvement, well-designed studies with extended time frame are required.